Edo Period Masculinity In Sugawara Denju Tenarai Kagami (1746) - Ariefa, Nina Alia (IZUMI, 2023)
As part of cultural documentation, literary works have the ability to record the conditions of the times and society in a nation, including gender issues as values that are built, emphasized, and disseminated in the community. As a period characterized by feudal society under the leadership of the Tokugawa clan, the Edo period (1603-1868) is known as the golden age of the development of traditional Japanese culture. Through a study of the play Sugawara Denju Tenarai Kagami (1746) which is one of the masterpieces of the Edo period, this study reveals the representation of masculinity that shows a hierarchical social construction between men and women. The method used in this study is a qualitative analysis through a gender approach from Wharton (2005) and Lindsey (2016), as well as a feminist criticism approach from Tyson (2015). The construction of masculinity in this play highlights the depiction of men as knights, which are associated with courage, loyalty, integrity, toughness and self-respect. In addition, the concept of masculinity is depicted as strongly tied to the determination of hierarchical and patriarchal social structures, as well as being a reflection of the gender ideology of the Edo period which puts the superiority of men as the central figure in socio-cultural life. The depiction of male qualities and characters that outperform female characters in this text shows the text’s strategy in strengthening the patriarchal paradigm, and clearly shows the function of this text as a locus for strengthening the implementation of patriarchy in the Edo period. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor